Характеристика базових понять іншомовної підготовки майбутніх фахівців засобами цифрових освітніх ресурсів - Ясногурська Людмила; Yasnogurska Lyudmyla (Видавництво «Код», 2025)
Резюме. У статті визначено характеристику базових понять іншомовної підготовки майбутніх фахівців засобами цифрових освітніх ресурсів. Характерними особливостями навчання з використанням засобів інформаційних технологій, на відміну від традиційної системи, є поступальний та прогресивний характер змін технологій навчання. Зазначимо, що точної, стандартизованої дефініції терміну «іншомовна підготовка студентів» немає, але у науковій літературі фіксуються такі спільні риси.

Abstract. The article defines the characteristics of the basic concepts of foreign language training of future specialists using digital educational resources. The characteristic features of training using information technology, in contrast to the traditional system, are the progressive and progressive nature of changes in learning technologies. It should be noted that there is no exact, standardized definition of the term «foreign language training of students», but the following common features are recorded in the scientific literature. Mastery of modern information and communication technologies is becoming a necessary attribute of a specialist of any profile, ensuring a certain information and functional independence. The characteristic features of digital educational resources are: interactivity and availability at any time; multimedia; the possibility of self-control and assessment of knowledge; integration with other digital services. Digital educational resources in foreign language training of students are a set of digital educational and information tools that are used in the process of learning a foreign language in order to form communicative foreign language competence. In our opinion, digital educational resources in foreign language training of specialists are a complex of information learning tools, software materials, online platforms, multimedia materials and interactive tools that are necessary for the effective organization, promotion and improvement of the process of learning a foreign language. It helps to form foreign language communicative competence of specialists, expand listening, speaking, reading and writing skills, create conditions for individualization, motivation and selfeducation of students of higher education institutions, and serve as a model for the implementation of new technologies for teaching foreign languages, which combine traditional methods with the prospects of information and communication technologies.
Characteristics of the basic concepts of foreign language training of future professionals through digital educational resources
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: іншомовна підготовка; майбутні фахівці; цифрові освітні ресурси; вища освіта; компетентність